2019
DOI: 10.1021/acschemneuro.9b00572
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Structure of RNA Monomeric G-Quadruplex Containing ALS and FTD Related G4C2 Repeat and Its Binding with TMPyP4 Probed by Homology Modeling based on Experimental Constraints and Molecular Dynamics Simulations

Abstract: The G-quadruplex-forming hexanucleotide repeat expansion (HRE), d(G4C2) n , within the human C9orf 72 gene is the root cause for familial amyotrophic lateral sclerosis−frontotemporal dementia (ALS-FTD). A recent study has shown that TMPyP4 has good potential to work as a RNA G-quadruplex binder in treating ALS and FTD. Although the high-resolution structure of the monomeric DNA antiparallel G-quadruplex form of the monomeric hexanucleotide repeat was recently solved, the RNA parallel G-quadruplex structure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 87 publications
1
8
0
Order By: Relevance
“…Our finding that TMPyP4 target elongation but not initiation of G 4 C 2 RAN translation is fully compatible with previous reports describing that C9orf72 RAN translation initiates at near cognate codons in the 5′ proximal region ( i.e. , outside) of G 4 C 2 repeat ( 42 , 43 , 44 , 45 ), and TMPyP4 preferentially interacts with RNA G 4 C 2 repeat sequence through G-quadruplex structure ( 52 , 62 , 63 ).…”
Section: Discussionsupporting
confidence: 92%
“…Our finding that TMPyP4 target elongation but not initiation of G 4 C 2 RAN translation is fully compatible with previous reports describing that C9orf72 RAN translation initiates at near cognate codons in the 5′ proximal region ( i.e. , outside) of G 4 C 2 repeat ( 42 , 43 , 44 , 45 ), and TMPyP4 preferentially interacts with RNA G 4 C 2 repeat sequence through G-quadruplex structure ( 52 , 62 , 63 ).…”
Section: Discussionsupporting
confidence: 92%
“…Of course, this does not necessarily apply to other loop types in other G4s, which may affect the binding differently. Spontaneous binding of a ligand to the loops, direct binding to terminal G-quartets, and sliding of ligands from the loops along the backbone to the terminal G-quartets have been observed in MD simulations of G4s with other ligands, including telomestatin and BRACO19. A decisive loop-assisted delivery of RHPS4 to the partially exposed 3′-quartet of the human telomeric hybrid-1 type G4 has been reported, in which the propeller loop with the bound ligand significantly changed its conformation and brought the ligand closer to the quartet ( cf . supplementary movie “Hybrid_G4_2HY9_02” in ref ), but to the best of our knowledge, the direct loop-to-quartet ligand delivery that we observed in our study has not been reported yet.…”
Section: Discussionmentioning
confidence: 97%
“…Spontaneous binding of a ligand to the loops, direct binding to terminal G-quartets and sliding of ligands from the loops along the backbone to the terminal G-quartets has been observed in MD simulations of G4s with other ligands, including telomestatin and BRACO19. [94][95][96][97][98][99][100][101][102] A decisive loop-assisted delivery of RHPS4 to the partially exposed 3ʹ-quartet of the human telomeric hybrid-1 type G4 has been reported, in which the propeller loop with bound ligand significantly changed its conformation and brought the ligand closer to the quartet (Cf. Supplementary Movie "Hybrid_G4_2HY9_02" in ref.…”
Section: Discussionmentioning
confidence: 99%
“…The GGGGCC HRE RNA has been shown to form G-quadruplexes in vitro ( Fratta et al, 2012 ; Reddy et al, 2013 ; Conlon et al, 2016 ), and these structures have been observed in the postmortem tissue of ALS patients ( Conlon et al, 2016 ). Few studies have delved into the structure of purified (GGGGCC) n RNA under various conditions ( Dodd et al, 2016 ; Mulholland et al, 2020 ), though the physiological structure of this RNA remains elusive. It is known that some subset of the HRE RNA is present in the form of foci, which each contain a single highly structured RNA molecule ( Liu et al, 2017 ), though studies of the structures that soluble HRE RNA adopts have yet to be performed.…”
Section: C9orf72mentioning
confidence: 99%